Unsettling Translation : Studies in Honour of Theo Hermans. - Baker, Mona. (Milton : Taylor & Francis Group, 2022)
This collection engages with translation and interpreting from a diverse but complementary range of perspectives, in dialogue with the seminal work of Theo Hermans. It is important reading for translation scholars, researchers and advanced students on courses covering key trends and theories in translation studies.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books